2016
DOI: 10.3109/03009742.2015.1124452
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid proteins are required for the induction of interleukin-1β production by monosodium urate crystals

Abstract: This study shows that the SF of inflammatory arthritis patients, including gout patients, contains proteins required for the induction of IL-1β by MSU crystals in macrophages whereas lipids are not involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Additionally, the IL-1β level in the synovial membrane was positively correlated with OA grade, and joint space width was negatively correlated with joint activity (31,32). Additionally, IL-1β was detected in human OA cartilage, especially in early stage OA and the IL-1β level in the synovial fluid was correlated with synovial fluid uric acid level in patients with KOA; thus, it was concluded that synovial fluid uric acid could be a danger signal that contributes to increasing KOA risk through NLRP3-mediated inflammasome (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the IL-1β level in the synovial membrane was positively correlated with OA grade, and joint space width was negatively correlated with joint activity (31,32). Additionally, IL-1β was detected in human OA cartilage, especially in early stage OA and the IL-1β level in the synovial fluid was correlated with synovial fluid uric acid level in patients with KOA; thus, it was concluded that synovial fluid uric acid could be a danger signal that contributes to increasing KOA risk through NLRP3-mediated inflammasome (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…The necessity for a second factor to activate the MSU crystal-induced inflammation was reinforced by a recent in vitro study that evaluated the effect of IL-1β production and IL-1β mRNA expression by macrophages/monocytes on exposure to MSU crystals ( 40 ). Exposure of human macrophages/monocytes to MSU crystals alone did not induce the release of IL-1β, but required the presence of synovial fluid (supernatant and free of cells) from patients with inflammatory arthritis ( 40 ). On fractionation analysis, it was demonstrated that the MSU crystal co-stimulus was contained in the protein fraction but not in the lipidic fraction of synovial fluid ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of human macrophages/monocytes to MSU crystals alone did not induce the release of IL-1β, but required the presence of synovial fluid (supernatant and free of cells) from patients with inflammatory arthritis ( 40 ). On fractionation analysis, it was demonstrated that the MSU crystal co-stimulus was contained in the protein fraction but not in the lipidic fraction of synovial fluid ( 40 ). However, the protein from synovial fluid in this study acted as a co-stimulatory factor rather than a “primer” because pre-treatment of macrophages/monocytes with synovial fluid did not result in the production of IL-1β ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, it became clear that purified crystals alone could not induce IL-1but that an additional stimulus was needed in vitro to generate IL-1 (Giamarellos-Bourboulis et al, 2009). Further ex vivo models identified free fatty acids (Joosten et al, 2010) and synovial fluid (SF) proteins (Scanu et al, 2016) as important triggers of IL-1 release.…”
Section: Inflammasome Il-1 and Il-ra In Crystal-induced Arthropathiesmentioning
confidence: 99%